The myth of rights the purposes and limits of constitutional rights - Bhagwat, Ashutosh A. (New York ; Oxford : Oxford University Press, 2010)
What is a constitutional right? If asked, most Americans would say that it is an entitlement to act as one pleases, i.e. that rights protect autonomy. That understanding, however, is wrong and is, indeed, 'The Myth of Rights'. This book addresses the constitutional issues posed in these and many other areas of law and public policy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Civil rights -- United States